Nepalese Teachers’ Perceptions on Integrating Technology in English Language Teaching - Durga Raj Bhusal (English Language Teaching and Research Journal (ELTAR-J), 2020)
The best innovative endeavor the teachers of English have assumed so far is to integrate technology in ELT classrooms, to improve increase self-directed learning, learners’ motivation, integrated language skills, and self-learning environment. Accordingly, the integration of ICT in teaching and learning brings innovative learning environments and helps students to deal with knowledge in active, self-directed, and constructive ways. This paper explores the techniques of integrating information communication technology (ICT) in English language classrooms within the theoretical framework of connectivism. It demonstrates that integrating ICT tools in English language classrooms not only constitutes communicative and interactive sound skills but also the opportunity to construct ICT skills to make learners competitive in 21st-century skills. It further shows English language teachers’ in-depth thoughts, beliefs, opinions, and practices of using ICTs in their classrooms. Moreover, it reveals that English language textbooks undervalue integrating ICT lessons and teachers are reluctant to use them and give main priority to the other grammatical and linguistic features.